Temporal Trends in Inpatient Oncology Census Before and During the COVID‐19 Pandemic and Rates of Nosocomial COVID‐19 Among Patients with Cancer at a Large Academic Center. (18th May 2021) - Zubiri, Leyre; Rosovsky, Rachel P.; Mooradian, Meghan J.; Piper‐Vallillo, A.J.; Gainor, Justin F.; Sullivan, Ryan J.; Marte, Daniel; Boland, Genevieve M.; Gao, Xin; Hochberg, Ephraim P.; Ryan, David P.; McEwen, Corey; et al.
Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic has significantly impacted health care systems. However, to date, the trend of hospitalizations in the oncology patient population has not been studied, and the frequency of nosocomial spread to patients with cancer is not well understood. The objectives of this study were to evaluate the impact of COVID‐19 on inpatient oncology census and determine the nosocomial rate of COVID‐19 in patients with cancer admitted at a large academic center. Materials and Methods: Medical records of patients with cancer diagnosed with COVID‐19 and admitted were reviewed to evaluate the temporal trends in inpatient oncology census during pre–COVID‐19 (January 2019 to February 2020), COVID‐19 (March to May 2020), and post–COVID‐19 surge (June to August 2020) in the region. In addition, nosocomial infection rates of SARS‐CoV‐2 were reviewed. Results: Overall, the daily inpatient census was steady in 2019 (median, 103; range, 92–118) and until February 2020 (median, 112; range, 102–114). However, there was a major decline from March to May 2020 (median, 68; range, 57–104), with 45.4% lower admissions during April 2020. As the COVID‐19 surge eased, the daily inpatient census over time returned to the pre–COVID‐19 baseline (median, 103; range, 99–111). One patient (1/231, 0.004%) tested positive for SARS‐CoV‐2 13 days after hospitalization, and it is unclear if it was nosocomial or community spread. Conclusion: In this study, inpatient oncology admissions decreased substantially during the COVID‐19 surge but over time returned to the pre–COVID‐19 baseline. With aggressive infection control measures, the rates of nosocomial transmission were exceedingly low and should provide reassurance to those seeking medical care, including inpatient admissions when medically necessary. Implications for Practice: The COVID‐19 pandemic has had a major impact on the health care system, and cancer patients are a vulnerable population. This study observes a significant decline in the daily inpatient oncology census from March to May 2020 compared with the same time frame in the previous year and examines the potential reasons for this decline. In addition, nosocomial rates of COVID‐19 were investigated, and rates were found to be very low. These findings suggest that aggressive infection control measures can mitigate the nosocomial infection risk among cancer patients and the inpatient setting is a safe environment, providing reassurance. Abstract : To understand the overall impact of COVID‐19 on health care delivery in the oncology setting, this study evaluated the inpatient oncology census, in comparison to historical data and infusion volume, at an institution with a high volume of COVID‐19 admissions.